Leksikon dan Fungsi Budaya dalam Gara`i di Provinsi Gorontalo - Anwar Manto; Ivan R.B. Kaunang; Erenst Mantiri (Ideas Publishing, 2023)
Lexicon and specific anthropological linguistics reveal the cultural description of the Gorontalo people in gara'i through lingual codes. The method used is descriptive qualitative, namely all research data in the form of words, phrases, clauses, and sentences. The results of the research and discussion found: (a) out of 30 gara`i there are 16 noun lexicons, 20 verbs containing cultural information and gara`i are constructed by morphophonemic processes of omission, addition, phoneme change and affixation including prefixes, suffixes, and infixes (b) function in gara`i consists of pragmatic, ethical and historical functions.